Static Analysis - Alpuente, María (Springer, 2017)
This book constitutes the refereed proceedings of the 15th International Symposium on Static Analysis, SAS 2008, held in Valencia, Spain in July 2008 - co-located with LOPSTR 2008, the International Symposium on Logic-based Program Synthesis and Transformation, PPDP 2008, the International ACM SIGPLAN Symposium on Principles and Practice of Declarative Programming, and PLID 2008, the International Workshop on Programming Language Interference and Dependence.